2022
DOI: 10.3390/sports10020019
|View full text |Cite
|
Sign up to set email alerts
|

Chest Exercises: Movement and Loading of Shoulder, Elbow and Wrist Joints

Abstract: Injuries to the shoulder are very common in sports that involve overhead arm or throwing movements. Strength training of the chest muscles has the potential to protect the shoulder from injury. Kinematic and kinetic data were acquired in 20 healthy subjects (age: 24.9 ± 2.7 years) using motion capture, force plates for the bench press exercises and load cells in the cable for the cable pulley exercises with 15% and 30% of body weight (BW). Joint ranges of motion (RoM) and joint moments at the shoulder, elbow a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 29 publications
(46 reference statements)
3
8
0
1
Order By: Relevance
“…Of the 1378 respondents, n = 732 (52,5%) answered having complaints in relationship to the tness training in a gym and n = 655 (47,4%) denied that. We can show a signi cant positive in uence of the female gender on the absence of pain which is comparable to other studies dealing with gender differences in sports [20][21][22][23]. Training plan design seems to play a crucial role in pain prevention.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Of the 1378 respondents, n = 732 (52,5%) answered having complaints in relationship to the tness training in a gym and n = 655 (47,4%) denied that. We can show a signi cant positive in uence of the female gender on the absence of pain which is comparable to other studies dealing with gender differences in sports [20][21][22][23]. Training plan design seems to play a crucial role in pain prevention.…”
Section: Discussionsupporting
confidence: 87%
“…In our research, we found few similarly designed studies that focus on the recreational tness sport. However, some studies deal with this topic in speci c population groups such as sports students or focus on speci c exercises [3,[5][6][7][8][9][10][11]. Different authors agree that athletes often have very speci c injury patterns, which also require a correspondingly tailored therapy.…”
Section: Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The shoulder horizontal abduction and elbow extension peak moments measured in this study (Tables 3 and 4) were similar to shoulder horizontal abduction (123.0 6 48.50 N) and elbow extension peak moments (22.15 6 8.35 N•m) in a study by Mausehund et al (23) at 80% of 1RM. Parallel to a previous study, peak moments for shoulder abduction, elbow extension, and ulnar deviation significantly increased with an increase in weight (31). Electromyography activity of the anterior deltoid, triceps brachii, and pectoralis major all increased as weight increased, which is similar to results found in a study on the effect of weight on the bench press by Kr ól and Gołaś (17).…”
Section: Discussionsupporting
confidence: 86%
“…It is not clear why this was the case. Schütz et al (31) also found differences in peak joint moments across different bench press weight conditions, but these researchers did not measure average joint moments. However, others have also found inconsistency when comparing average and peak joint moments.…”
Section: Discussionmentioning
confidence: 99%